Steady State Diagrams for Circulating Fluidzed Beds - Wirth, Karl-Ernst (Preprints 3rd International Conference on Circulating Fluidized Beds, 1990)
Circulating fluidization is a growing new  technology in  many fields where good  fiuid-solid contact is required. Combustion. power generation, catalytic reactions, drying. waste  incineration and iron ore prereduction ate good examples of its application. New  material processing and other fine technology  area will be  as well included soon. The Third International Conference on Circulating Fluidized Beds (ICCFB- 3) was held at  Nagoya.  Japan. from October 15 to 18. 1990. organized by the Society of Chemical Engineers. Japan in  cooperation with the secretariat of ICCPB. In  this conference the attendants vould have the good balances between academic and  industrial subjects as well as between fundamentals and applications or developments. There were 113  papers from  twenty countries and approximately  133  participants from foreign counlries and 150 from  Japan. To establish common Understandings on the state of  arts in  the  CFB society and at  the same time to  encourage as many people to present their papers or opinions, plenary  lectures. combined oral 8 poster sessions, and workshops were assembled. The conference  language was English. All papers to  be presented at the conference  were handed to  all attendants in  a  form of bounded  loose leaves (preprints). The conference site Nagoya is a cozy city located at  the center of pacific  metropolitan belt of the Mainisland  of Japan. People in  the greater Nagoya  area have been proud of her production of  three SAMURAI heroes in  the age of  feudalistic civil war who after all unified  Japan and opened The Tokugara Era that  lasted for 268 years. Nagoya is surrounded by many  basic  and high-tech  industries  including  automobiles. aircrafts,  electronics, iron and steel,  petroleum  and  petrochemicals. ceramics. etc. Resort and picturesque areas including  Japan Alps mountains.  Kyoto.  Nara  and Ise-Shima are all very close from  Nagoya. within one and half hours travel (by train) or at most  three hours by  car via highways. Business trips to Tokyo and/or Osaka are again very simple if they vere made from Nagoya (two hours to Tokyo and one hour and half to Osaka by  Super Express Hikari)
UnivIS-Import:2015-04-16:Pub.1990.tech.ITC.mechve.steady
Keywords: circulating; fluidized; bed